Some Practical and Biotechnological Methods for Improving Reproduction Traits in Sheep - Novotniné Dankó, Gabriella (Acta Agraria Debreceniensis, 2003)
However, reproduction in sheep is seasonal, many breeds of sheep are able to mate not only in autumn, but out-of-season as well. The main factor determining seasonality is the photoperiod, but other factors can influence reproductive pattern, such as genetics, management practices and social cues. The fertility of spring and early summer breeding is usually lower; this imposes the need for alternative methods (e.g. hormonal treatments, biotechnological practice), to increase the conception rate. The author summarize the main practical techniques and biotechnological methods for controlling reproduction completed with some own experimental results in connection with different topics.